2019
DOI: 10.1002/cbin.11257
|View full text |Cite|
|
Sign up to set email alerts
|

High expression of ALDH1A3 might independently influence poor progression‐free and overall survival in patients with glioma via maintaining glucose uptake and lactate production

Abstract: Recent studies have found that the acetaldehyde dehydrogenase 1A3 (ALDH1A3) gene is a marker of glioma stem cells. A total of 115 brain glioma specimens were collected and classified into grade I–IV, while non‐tumor brain tissue specimens, taken from 12 patients of vascular malformation surgery, were used as control. ALDH1A3 gene promoter methylation in glioma tissues was detected by pyrosequencing, while immunohistochemistry and western blot were used to detect ALDH1A3 protein expressions in different grades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Previous studies suggest that ALDH1A3 is closely associated with the colony formation, sphere formation, tumorigenesis, and angiogenic activity of cancer cells (15). High expression of ALDH1A3 predicts poor prognosis in glioma (18), melanoma (19), glioblastoma (20), and breast cancer (21). However, the role of ALDH1A3 has not so far been reported under physiological circumstances in PDAC cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggest that ALDH1A3 is closely associated with the colony formation, sphere formation, tumorigenesis, and angiogenic activity of cancer cells (15). High expression of ALDH1A3 predicts poor prognosis in glioma (18), melanoma (19), glioblastoma (20), and breast cancer (21). However, the role of ALDH1A3 has not so far been reported under physiological circumstances in PDAC cells.…”
Section: Discussionmentioning
confidence: 98%
“…studies on the correlation between PKM2 and its role in glioma (11,32,33), we studied the relationship between PKM2 and glioma. Although previous studies have shown the effects of PKM2 inhibition of glioma cells (13,17,18,34), we attempted to identify the mechanism of PKM2 inhibition. We also anticipated that our novel findings about the role of PKM2 in glioma might facilitate the application of PKM2-targeting in glioma in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate kinase M2 (PKM2) is a key rate-limiting enzyme of glycolysis in cancer cells. It has been demonstrated to contribute to the genesis and proliferation of glioma cells (13), and has thus recently gained much attention.…”
mentioning
confidence: 99%
“…An increasing body of evidence suggests that ALDHs target inhibitors could inhibit stem-like cell proliferation of gliomas (18,34,35). Furthermore, ALDH1A3 could reportedly affect glioma glucose metabolism and is recognized as a stem-like cells biomarker (36,37). Besides, ALDH1A1 and ALDH1A2 have been documented as glioma migration-associated genes (38)(39)(40), while ALDH1A1 also participated in GBM resistance to temozolomide (17,19).…”
Section: Discussionmentioning
confidence: 99%